2021
DOI: 10.3390/molecules26030607
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Jamaican Medicinal Plants and Isolated Bioactive Compounds

Abstract: Plants have had historical significance in medicine since the beginning of civilization. The oldest medical pharmacopeias of the African, Arabian, and Asian countries solely utilize plants and herbs to treat pain, oral diseases, skin diseases, microbial infections, multiple types of cancers, reproductive disorders among a myriad of other ailments. The World Health Organization (WHO) estimates that over 65% of the world population solely utilize botanical preparations as medicine. Due to the abundance of plants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 71 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…The anti-human Influenza A activity of Hibiscus sabdariffa L. (sorrel) has been attributed to a number of phytochemical constituents, including delphinidin-3-O-sambubioside [92]. In silico studies have shown that delphinidin-3,5-diglucoside interacts via hydrogen bonding with Gly143, His163, His164, Glu166, Gln189, Thr190, and Gln192 and π-π interaction with His41 of the main protease Mpro of SARS-CoV-2, which suggests that the compound can be useful in inhibiting viral replication through inhibition of Mpro [93].…”
Section: Flavonoids-classification Structure and Anti-viral Activitiesmentioning
confidence: 99%
“…The anti-human Influenza A activity of Hibiscus sabdariffa L. (sorrel) has been attributed to a number of phytochemical constituents, including delphinidin-3-O-sambubioside [92]. In silico studies have shown that delphinidin-3,5-diglucoside interacts via hydrogen bonding with Gly143, His163, His164, Glu166, Gln189, Thr190, and Gln192 and π-π interaction with His41 of the main protease Mpro of SARS-CoV-2, which suggests that the compound can be useful in inhibiting viral replication through inhibition of Mpro [93].…”
Section: Flavonoids-classification Structure and Anti-viral Activitiesmentioning
confidence: 99%
“…Among viral infections, psychoactive THC has been found advantageous from anecdotal and clinical evidence for the people suffering from acquired immunodeficiency syndrome (AIDS). The benefits do not come from virus inhibition or reduction of mortality but improvement in the host’s quality of life [ 145 ]. Dronabinol, a synthetic analog of THC, has been approved by the United States Food and Drug Administration (FDA) to mitigate wasting syndrome and loss of appetite of AIDS patients [ 146 ].…”
Section: Antiviral Activity: Special Focus On Sars-cov-2mentioning
confidence: 99%
“…Bioactive compounds extracted from various parts of these plants are responsible for the therapeutic effects of phyto-antivirals which include anthraquinones, coumarins, flavonoids, alkaloids etc. [4]. According to the World Health Organization (WHO), more than 80% of the population in Africa and over 65% of the world population uses herbal medicine to meet their primary health care needs [4,5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4]. According to the World Health Organization (WHO), more than 80% of the population in Africa and over 65% of the world population uses herbal medicine to meet their primary health care needs [4,5 ]. Herbal medicines are safe, effective, and have fewer side effects compared to allopathic medicines [5].…”
Section: Introductionmentioning
confidence: 99%